Collaborative Governance of Vocational Middle School Education Planning to Meet the Needs of the Business and Industry World in Banten Province - Nyoto Suwignyo; Muchlis Hamdi; Hadi Prabowo; Sampara Lukman (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The implementation of development in Indonesia is directed at achieving the ideals of the State of Indonesia to become a sovereign, advanced, just and prosperous country. One of the efforts to achieve this is through the implementation of education which is the responsibility of the Central Government and the Provincial/Regency/City Governments, where the Provincial Government has the authority to administer General High School and Vocational High School Education. The Banten Provincial Government in supporting the implementation of education, especially vocational education, is carried out through Vocational Revitalization in order to meet the needs of the Business and Industrial World (DUDI) which require collaborative governance planning. This study aims to analyze collaborative governance of vocational education planning in Banten Province and develop collaborative governance strategies for vocational education planning in Banten Province. This research focuses on collaborative governance that occurs in every stage of education planning for Vocational High Schools (SMK) in Banten Province in 2020-2021. Collaborative governance of Vocational Education planning in Banten Province is carried out using a qualitative approach with descriptive analysis methods. Data obtained through documentation, interviews and observations. The researcher analyzes collaborative governance that is contained in each stage of planning for Vocational High Schools in Banten province by using indicators of facilitative leadership, institutional designs, which will encourage a collaborative process in education planning for Banten Province Vocational High Schools. at each planning stage which consists of five stages, namely develop the plan, translate the plan, plan operations, execute the plan, as well as monitor and learn and analyze the involvement of actors in each stage of planning for Vocational High Schools in Banten Province. The results of the analysis show that collaborative management of vocational education planning in Banten Province is not optimal, where the role of actors is still partial and planning and budgeting from CSR funds or other funding sources have not been included in regional planning documents.